ANALYSIS OF THE ROLE OF BUMDes (Village Owned Enterprises) IN VILLAGE COMMUNITY EMPOWERMENT (Case Study of BUMDes Makmu Beusaree Lambro Deyah Village, Kuta Baro District, Aceh Besar District) - Safrida, Safrida; Handayani, Sri; Zakiah, Zakiah; Amalia, Rauzah (CV. Radja Publika, 2022)
The role of BUMDes has a positive impact on communities and villages in terms of improving the economy and community welfare by establishing several business units, namely cattle fattening, catfish farming, house rental, terraces, and shop houses. However, the presence of BUMDes Makmu Beusaree has not played a role in increasing people's income, employment, and reducing poverty. But for community participation and contribution and increasing community knowledge and skills, BUMDes has played a role. The income of the community after joining BUMDes increased from the first category of Rp. 0-1,000,000 to the second category of Rp. 1,000,000-2,000,000, but BUMDes has not had a significant effect on increasing income because only people who join BUMDes experience an increase in income. The active workforce absorbed by BUMDes is 14 people. After the existence of BUMDes, the poverty rate decreased by 6%. The participation and contribution of the Lambro Deyah community to BUMDes is very good, as seen from the average percentage interval, which is 84.70% of the community participating and contributing to BUMDes. The increase in knowledge and skills carried out by BUMDes management is by providing training to BUMDes members and the community such as training and socialization of making animal feed from straw.